Log in to add a comment

## Answers

=x/2+3y/2 + 5x-10y/3=-3/2

11x/2 - 11/6y=-3/2

multiply this equation by 6

33x-11y=-9 let this is equation 1

5/4(x+2y)-3/5(3x-2y)=61/60 let this equation is 2nd equation

5/4x +5/2y - 9/5x-6/5y=61/60

(25x-36x)/20 + (25y-12y)/10 = 61/60

multiply this equation by 60

3(-11x) + (13y)6=61

-33x+78y=61 let this eqution is second equation

33x-11y=-9

-33x+78y=61

add these two eqution

0+68y=52

y=68/52 put the value of y in 1st equation

33x-11y=-9

33x-11(68/52)=-9

33x-748/52=-9

33x*52-748=-9*52

1716x =-468+748

1716x=300

x=300/1716

x/2 + 3y/2 + 15x/3 - 5y/3 = -3/2

33x - y = -9.............(1)

5/4(x+2y) - 3/5(3x-2y) = 61/60

-11x + 74y = 61/3.................(2)

From eq. 1 y = 9 + 33x

From eq. 2 y = 61 - 33x / 222

THEREFORE, 9 + 33x = 61 -33x / 222 {method of similarity}

Solve further